2022
DOI: 10.3389/fphar.2022.898623
|View full text |Cite|
|
Sign up to set email alerts
|

Case Report: Durable response to immuno-chemotherapy in a case of ROS1 fusion-positive advanced lung adenocarcinoma: A case report

Abstract: Immune checkpoint inhibitors (ICIs) have greatly transformed the treatment and improved the prognosis for patients with non-small cell lung cancer (NSCLC) without driver gene alterations. However, the effects of ICI combination therapy in ROS1 fusion-positive NSCLC remains unclear. Herein, we present a case with ROS1 fusion-positive NSCLC treated with ICI plus chemotherapy. The patient achieved a continuous partial response (PR) to ICI plus chemotherapy and a more than 35 months progression free survival. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, The efficacy of immunotherapy in ROS1 fusion NSCLC patients remains to be further studied. We have reported a ROS1 positive NSCLC patient, who achieved a continuous PR to immunotherapy plus chemotherapy and a more than 35 months PFS ( 42 ). Nevertheless, another study indicated that ROS1 fusion NSCLC patients treated with immunotherapy alone displayed an unsatisfactory ORR of 16.7% ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, The efficacy of immunotherapy in ROS1 fusion NSCLC patients remains to be further studied. We have reported a ROS1 positive NSCLC patient, who achieved a continuous PR to immunotherapy plus chemotherapy and a more than 35 months PFS ( 42 ). Nevertheless, another study indicated that ROS1 fusion NSCLC patients treated with immunotherapy alone displayed an unsatisfactory ORR of 16.7% ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang's published work on Nature describes that ROS1 rearrangements present actionable therapeutic targets for non-small cell lung cancer (NSCLC). [18][19][20][21][22] Chen's published work on Oncotarget describes that NKX2-1 may suppress lung adenocarcinoma progression via impeding TGF-β-induced epithelialto-mesenchymal transition (EMT) due to Elevated expression of E-cadherin and occludin targeted by NKX2-1 impeded migration and induced apoptosis in lung cancer cells. [23][24][25][26][27] According to Moeller's published work in Cancer Control journal, patients with lung adenocarcinoma not expressing TTF1 have a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%